Inter-objectivity and the Birth of New Materialism: How to Understand "Objects" in a Metaverse. - Lan, Jiang (Critical Arts: A South-North Journal of Cultural & Media Studies)
The metaverse brings us not only a flashy phase of new technologies, but also forces us to rethink some fundamental philosophical concepts, among which the theory of objects becomes an important issue in the metaphysical reflection of the metaverse. Heidegger gives objects a mysticism of externality in terms of the Zuhandenkeit and Spiegle-Spiel of earth and sky, divinities and mortals, while Baudrillard's critique of the system of objects and the political economy of symbols turns objects into nihilism under the system of symbols. How to retain the status of objects in the metaverse without allowing them to go simultaneously metaphysical and nihilistic requires the proposal of a new materialism. We propose a law of imitation of things based on Tarde's law of imitation between persons, forming an inter-objectivity as opposed to an inter-subjectivity, and in this way seeing objects as a system of inter-objectivity with an active generation of associations, in which both persons and things form correspondences, and in which the whole network of all objects is formed in relation to each other. This is the birth of materialism, and a possible way of understanding things under our metaverse.